Extraction, characterization and anti-oxidant activity of polysaccharide from red Panax ginseng and Ophiopogon japonicus waste - Kang, Jia; Zhao, Jue; He, Lan-Fang; Li, Li-Xia; Zhu, Zhong-Kai; Tian, Meng-Liang (Frontiers in Nutrition, 2023)
Red ginseng and Ophiopogon japonicus are both traditional Chinese medicines. They have also been used as food in China for thousands of years. These two herbs were frequently used in many traditional Chinese patent medicines. However, the carbohydrate compositions of these two herbs were not normally used during the production of said medicine, such as Shenmai injection, resulting in a large amount of waste composed of carbohydrates. In this study, the extraction conditions were optimized by response surface methodology. The Shenmai injection waste polysaccharide was extracted by using distilled water that was boiled under the optimized conditions. The Shenmai injection waste polysaccharide (SMP) was thereby obtained. SMP was further purified by anion exchange chromatography and gel filtration. With this method, a neutral polysaccharide fraction (SMP-NP) and an acidic polysaccharide fraction (SMP-AP) were obtained. The results of structure elucidation indicated that SMP-NP was a type of levan, and SMP-AP was a typical acidic polysaccharide. SMP-NP exhibited potential stimulation activity on the proliferation of five different Lactobacilli strains. Therefore, SMP-AP could promote the antioxidant defense of IPEC-J2 cells. These findings suggest that Shenmai injection waste could be used as a resource for prebiotics and antioxidants.